2018
DOI: 10.1038/s41598-018-25704-1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental suitability models predict population density, performance and body condition for microendemic salamanders

Abstract: Species can show strong variation of local abundance across their ranges. Recent analyses suggested that variation in abundance can be related to environmental suitability, as the highest abundances are often observed in populations living in the most suitable areas. However, there is limited information on the mechanisms through which variation in environmental suitability determines abundance. We analysed populations of the microendemic salamander Hydromantes flavus, and tested several hypotheses on potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 68 publications
3
68
1
Order By: Relevance
“…In such areas predator pressure for this salamanders is generally low, and almost no closely related taxa (i.e., urodela species) are exploiting the same environment, thus limiting the occurrence of intraspecific competition [ 76 , 77 ]. Our findings confirm that the feeding activity of individuals is higher in the areas close to the cave entrance [ 70 ], being thus in agreement with the habitat segregation hypothesis [ 72 ]…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In such areas predator pressure for this salamanders is generally low, and almost no closely related taxa (i.e., urodela species) are exploiting the same environment, thus limiting the occurrence of intraspecific competition [ 76 , 77 ]. Our findings confirm that the feeding activity of individuals is higher in the areas close to the cave entrance [ 70 ], being thus in agreement with the habitat segregation hypothesis [ 72 ]…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of empty stomachs, and the number of prey per salamander, was strongly related with the distance from the cave entrance. Salamanders with empty stomachs and those with few prey items were more frequently found in the deepest sectors of caves [ 70 ]. Previous studies on Hydromantes salamanders showed spatial segregation, with different age classes and sexes exploiting different cave sectors [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many species do, however, appear to be more abundant at sites predicted to be more suitable by species distribution models (Lunghi et al, 2018;Weber, Stevens, Diniz-Filho, & Grelle, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Gradients in many abiotic factors (e.g. temperature, rainfall) are gradual and correlated with elevation (Lomolino, 2001;Lunghi et al, 2018). This means that elevational distance should be a better proxy for environmental distance than is spatial distance over large geographical areas, making "rare periphery" patterns theoretically more likely when measured elevationally (Brown, 1984;Van Couwenberghe et al, 2013) (Doughty & Goulden, 2008).…”
Section: Abundance Distributionsmentioning
confidence: 99%
See 1 more Smart Citation